First-principles investigation of the effect of interfacial compositions on the formation energies of Ω′ and T1 structures. (1st July 2023) - Yang, S.L.; Niu, Y.K.; Liu, J.Z.; Wilson, N.; Nie, J.F.
Abstract: The formation energies of the structures of Ω′ and T1 precipitates having different interfacial compositions are calculated by density functional theory. Our results show that the precipitates become much more energetically favourable to form when Ag and Mg and/or Li are present at their top and bottom layers. In such interfacial configurations, the role that Ag (with an atomic size similar to that of Al) plays is dominated by the chemical bonding effect, while the ability of larger atoms of Mg and Li to reduce the formation energy of the structure of Ω′ or T1 is mainly attributable to the elastic strain reduction. The findings of the effect of interfacial composition on the formation energies of the structures of Ω′ and T1 precipitates provide an insightful understanding on how to enhance the formation a specific strengthening constituent via micro-alloying addition of appropriate elements. Graphical abstract: Image, graphical abstract